ANALISIS BUKU MATHEMATICS FOR JUNIOR HIGH SCHOOL GRADE VIII 1st SEMESTER (BILINGUAL) BERDASARKAN KRITERIA BELL - Beni, I Gede; Trapsilasiwi, Dinawati; Kristiani, Arika Indah (Kadikma, 2013)
Abstract.In recent years, it has published manybilingualmathematicstextbooksas the needsofschools withbilingualclasses. The qualityof bilingualmathematicstextbookscan be evaluated usingfourcriteriaaccording toBell. Book thatwere analyzedin this studytitledMathematicsForJuniorHighSchoolGradeVIII 1stSemester(Bilingual).The result of data analysis method shown the suitability ofthe mathematical content is very well withthe percentage of88.33%, the suitability ofthe teaching methods is enough withthe percentage of54,29%, the suitability ofthe physical characteristics is very well withthe percentage of 90,91%, and the suitability of teacher aids is enough withthe percentage 47,37% . KeyWords :Analysis ofBook,Bell’s criteria.